Dynamic scoring of tax reforms in the European Union - Salvador Barrios Cobos; Mathias Dolls; Anamaria Maftei; Andreas Peichl; Sara Riscado; Janos Varga; Christian Wittneben (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
In this paper, we present the first dynamic scoring exercise linking a multi-country microsimulation and DSGE models for all countries of the European Union. We illustrate our novel methodology analysing a hypothetical tax reform for Belgium. We then evaluate real tax reforms in Italy and Poland. Our approach takes into account the feedback effects resulting from adjustments in the labor market and the economy-wide reaction to the tax policy changes. Our results suggest that accounting for the behavioral reaction and macroeconomic feedback to tax policy changes enriches the tax reforms' analysis, by increasing the accuracy of the direct fiscal and distributional impact assessment provided by the microsimulation model for the tax reforms considered. Our results are in line with previous dynamic scoring exercises, showing that most tax reforms entail relatively smaller feedback effects in terms of the labor tax revenues for tax cuts benefiting workers, compared with the ones granted to firms.
urn:nbn:de:bsz:180-madoc-425690
Keywords: 330